2014
DOI: 10.1159/000358066
|View full text |Cite
|
Sign up to set email alerts
|

Netrin-1 Promotes Epithelial Sodium Channel-Mediated Alveolar Fluid Clearance via Activation of the Adenosine 2B Receptor in Lipopolysaccharide-Induced Acute Lung Injury

Abstract: Background: The epithelial sodium channel (ENaC) is the driving force for pulmonary edema absorption in acute lung injury (ALI). Netrin-1 is a newly found anti-inflammatory factor that works by activating the adenosine 2B receptor (A2BAR). Meanwhile, activated A2BAR has the potential to enhance ENaC-dependent alveolar fluid clearance (AFC). However, whether netrin-1 can increase ENaC-mediated AFC by activating A2BAR remains unclear. Objectives: To investigate the effect of netrin-1 on AFC in ALI and clarify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…The acute lung injury (ALI) induced by seawater aspiration had an acuter and rapider course than that induced by LPS [4,6,7,8]. The majority death induced by seawater aspiration happened within the first 6 h (Figure 2), which is greatly shorter than 40 h in LPS-induced ALI [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The acute lung injury (ALI) induced by seawater aspiration had an acuter and rapider course than that induced by LPS [4,6,7,8]. The majority death induced by seawater aspiration happened within the first 6 h (Figure 2), which is greatly shorter than 40 h in LPS-induced ALI [29].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia increases HIF-1α protein by elevating its protein stability but not by prompting its mRNA expression [4,6,7,8]. However, instillation of seawater increased not only HIF-1α protein but also its mRNA expression (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major signaling pathway of A 2B AR is suggested to be the pathway involving adenylyl cyclase (AC) that leads to an increase in intracellular cAMP levels and results in the subsequent activation of PKA and other cAMP effectors such as Epac (Peakman and Hill, 1994; Murakami et al, 2000; Sitaraman et al, 2001; Lynge et al, 2003; Fang and Olah, 2007; Darashchonak et al, 2014; He et al, 2014). However, the A 2B AR-Gq-PLC pathway also mediates several crucial functions of A 2B AR (Gao et al, 1999; Linden et al, 1999; Panjehpour et al, 2005), and A 2B AR further couples to the MAPK and arachidonic acid signaling pathways and regulates membrane ion channels probably through G-protein βγ subunits (Feoktistov et al, 1999; Jimenez et al, 1999; Schulte and Fredholm, 2003a,b; Donoso et al, 2005).…”
Section: Molecular Function and Cellular Localization Of A2barmentioning
confidence: 99%
“…Thus, DCC was proposed to mediate netrin signaling in axon growth and guidance independently of A 2B AR activation (Stein et al, 2001). Intriguingly, more recent studies have reported that netrin-1 attenuates neutrophil transmigration and hypoxia-induced inflammation (Rosenberger et al, 2009), alveolar fluid clearance (He et al, 2014), and diabetic nephropathy (Tak et al, 2013) and induces cancer-cell invasion (Rodrigues et al, 2007) in an A 2B AR-dependent manner. These results appear to support the general notion that A 2B AR mediates the function of netrin-1 at least in certain tissues.…”
Section: Deleted In Colorectal Carcinoma (Dcc) and Netrin-1mentioning
confidence: 99%